Understanding reading as a form of language-use: A language game hypothesis. (August 2016) - Wallot, Sebastian
Abstract: Reading research and research on conversation have followed different paths: While the research program for reading committed itself to a relatively static view of language, where objective text properties serve to elicit specific effects on cognition and behavior of a reader, research on conversation has embraced a language-use perspective, where language is primarily seen as a dynamic, context dependent process. In this essay I contrast these two perspectives, and argue that in order to reach a unified understanding of natural language – be it reading, talking, or conversing – one needs to adopt a language-use perspective. Furthermore, I describe how reading can be seen as a form of language-use, and how the current landscape of research on reading can be re-interpreted in terms of a dynamic, context-sensitive perspective on language. In particular, I propose that the concept of 'language games' serves as a good starting point to conceive reading as a form of language-use, describe how one can derive first concrete hypotheses by re-interpreting reading in terms of language games, and show how they can be readily operationalized using tools from dynamic systems analysis.